(untitled) (Zoological Archives: An International Journal, 2022)
Marine crustaceans – comprising decapods, copepods, cirripedes, isopods, amphipods, and euphausiids – represent one of the most ecologically and economically significant invertebrate groups in the world’s oceans, yet their taxonomy remains plagued by morphological convergence, intraspecific variation, and extensive synonymy that confounds biodiversity surveys, stock assessments, and biosecurity screening. DNA barcoding using the mitochondrial cytochrome c oxidase subunit I (COI) gene has transformed invertebrate species identification in terrestrial systems but faces specific challenges in marine environments: high genetic diversity within species, shallow COI divergences between recently diverged sister species, and the prevalence of cryptic species complexes that share morphological characters. This study presents the largest integrative DNA barcoding dataset for marine crustaceans yet assembled, combining COI barcoding with 16S rRNA and morphometric analysis for 4,247 specimens representing 847 species from 24 families collected at 184 stations across the North Atlantic, Mediterranean, and Northeast Pacific. Standard COI barcoding correctly identified 74.8% of specimens to species level against morphological voucher identifications. Integration of 16S rRNA data increased correct identification to 87.4%, and addition of morphometric data produced a combined correct identification rate of 94.7%. ASAP species delimitation identified 284 candidate cryptic species – a 33.5% increase in apparent diversity beyond the 847 morphologically recognised species – concentrated in the families Copepoda (47.4% putative cryptic taxa), Amphipoda (38.4%), and Decapoda (24.7%). A reference barcode library of 847 validated COI sequences is deposited in BOLD and GenBank to enable future specimen identification.